2010
DOI: 10.4238/vol9-2gmr784
|View full text |Cite
|
Sign up to set email alerts
|

A single nucleotide polymorphism in the coding region of bovine transferrin is associated with milk fat yield

Abstract: ABSTRACT. The bovine transferrin gene (TF) is located at 125 cM on bovine chromosome 1 (BTA1); it codes for transferrin, a glycoprotein that is highly conserved in many species and that is responsible for iron transport. The TF gene has been located in several QTL regions, and some transferrin classes have been associated with fat and milk yields. We analyzed by means of allele-specific oligonucleotide real-time PCR the c.1455A>G SNP in exon 12 of the TF cDNA sequence (accession number U02564), which induces a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Suggestive quantitative trait loci have been detected for fat yield at 50 cM (Casas et al, 2004). Sanz et al (2010) reported that SNP c.1455A>G in exon 12 of Tf had a significant association (P < 0.0006) with high fat production in Holstein-Friesian animals. However, in the present study, no significant associations of these SNPs with fat content were detected at the three loci in the populations analyzed (P > 0.05).…”
Section: Association Of Tf Gene Polymorphism With Milk and Health Tramentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestive quantitative trait loci have been detected for fat yield at 50 cM (Casas et al, 2004). Sanz et al (2010) reported that SNP c.1455A>G in exon 12 of Tf had a significant association (P < 0.0006) with high fat production in Holstein-Friesian animals. However, in the present study, no significant associations of these SNPs with fat content were detected at the three loci in the populations analyzed (P > 0.05).…”
Section: Association Of Tf Gene Polymorphism With Milk and Health Tramentioning
confidence: 99%
“…Many polymorphisms have been found in the bovine Tf gene (Ashton et al, 1964;Zhang et al, 2008;Sanz et al, 2010). Twelve co-dominant alleles of Tf have been identified from a single locus using starch gel electrophoresis.…”
Section: Introductionmentioning
confidence: 99%
“…Single-nucleotide polymorphisms have been found in the Tf gene; however, due to limited availability of data on SNPs and their association with infectious diseases, particularly mastitis, they need to be examined further [16,17]. SNPs also need proper validation regarding whether they have any association with bovine mastitis resistance/tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that genes, connected originally to health and development traits, like IL8, IL8R, CCL2, CCR2, can be associated with dairy performance. Polymorphisms found in the above-mentioned genes are connected to at least one of the five main performance traits: milk, protein and fat yield, protein and fat percentage (LeyvaBaca et al 2007, Chen et al 2010, Sanz et al 2010. Lactoferrin (LF), an iron-chelating protein, is present in many mammalian biological fluids, including milk.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is of great importance to discover associations between genes related with animal health and performance simultaneously. Other genes, like IGF1 and LF »ancestor gene« -TF, were proved to influence milk performance, despite their primary role in health, development or reproduction (Sanz et al 2010, Szewczuk et al 2012). This suggests the pleiotropic effect, or the existence of a linkage between genes coding for the non-productive traits and dairy performance traits.…”
Section: Introductionmentioning
confidence: 99%